Impact of body mass index on cryoablation of atrial fibrillation: Patient characteristics, procedural data, and long‐term outcomes. - Urbanek, Lukas; Bordignon, Stefano; Chen, Shaojie; Bologna, Fabrizio; Tohoku, Shota; Dincher, Matthias; Schulte‐Hahn, Britta; Schmidt, Boris; Chun, Kyoung‐Ryul Julian (Journal of Cardiovascular Electrophysiology, 2022)
Introduction: Ablation of atrial fibrillation in the context of obesity can be challenging. We sought to evaluate the role of cryoballoon pulmonary vein isolation (CB‐PVI) in obese patients with symptomatic atrial fibrillation (AF). Methods: Patients with a BMI ≥ 25 kg/m2 and symptomatic AF who underwent CB‐PVI were retrospectively enrolled. Three groups were defined (G1: BMI of 25–29 kg/m2; G2: BMI of 30–34 kg/m2; G3: BMI ≥ 35 kg/m2). Results: 600 patients were included (59% male; 66 ± 11 years old); 337, 149, and 114 were assigned to G1, G2, and G3, respectively. Acute procedural success was recorded in 99.7% of patients. Procedural and fluoroscopy time were comparable but the radiation dose was significantly higher in G3. Procedural complications were 3% in G1, 5.4% in G2, and 8.8% in G3 (p =.01). The overall freedom from AF after 1‐year was 77%. G3 had a significantly worse 1‐year success rate compared to G1 and G2 (G3: 66.5% vs. G1: 78.4%; p =.015 and vs. G2: 82.5%; p =.008) with reduced 1‐year success in paroxysmal AF (G1: 84.0%; G2: 86.3%; and G3: 69.6%) but not in persistent AF (G1: 68.7%; G2: 77.4%; and G3: 62.1%). G3 showed similar success rates irrespective of AF form (PAF: 69.6% vs. persAF 62.1%; p =.501). Conclusion: Cryoballoon ablation in obese patients can be effective with an acceptable safety profile, 77% of patients were in stable SR at 1 year. Severe obese patients (BMI ≥ 35) showed reduced procedural safety and 1‐year success rate. In association with life style modification, CB ablation may represent a strategy to enhance rhythm control in the context of obesity.